0608 Physician Prescribing Patterns for Patients With Narcolepsy Treated With Sodium Oxybate. (12th April 2019) - Roy, Asim; Ito, Diane; Morris, Susan; Profant, Judi; Menno, Diane; Bae, Charles
Abstract: Introduction: There is limited real-world data on physician prescribing practices for patients with narcolepsy treated with sodium oxybate (SXB) and physician guidance regarding dosing adjustments to accommodate changes in their patients' typical routines. Study goals were to understand SXB prescribing patterns in clinical settings and recommendations physicians may provide based on hypothetical patient scenarios. Methods: We conducted a cross sectional, web-based survey of 25 board-certified sleep medicine physicians currently treating ≥2 patients with narcolepsy (type 1 or 2) who have been on SXB for ≥6 months. Participants were recruited from physician panels. Participants were asked about their patients' usual SXB dosing regimens, frequency and reasons for SXB dosing-related discussions, preferred methods and perceived importance of adjusting SXB dosing. Descriptive statistics were used to summarize survey responses. Via telephonic voice response, participants were asked to provide dosing-related guidance for 4 hypothetical patient scenarios. Responses were analyzed thematically. Results: Of participants (N=25), 52% were neurologists, 44% psychiatrists and 4% neuropsychiatrists. Physicians reported currently treating a mean (±SD) of 25.4 (±27.2) patients with narcolepsy with SXB. Regarding usual dosing regimen, physicians reported 50.4% (± 30.3%) of their current patients were taking SXB twice-nightly, and 39% (±29.3%) once-nightly. 68% reported discussing an adjustment to usual SXB dosing to accommodate a change in patient routine. Drinking alcohol (65%) and travel (59%) were the most common reasons for adjusting SXB dosing. Guidance regarding adjusting total nightly dose (68%) and timing of doses (68%) were preferred recommendations for adjusting. The majority (88%) of physicians indicated that the ability to adjust SXB dosing was important and had a positive impact on their ability to provide care. For each hypothetical patient scenario, physicians provided a range of dosing adjustment recommendations to enable patients to accomplish goals. Conclusion: Physicians were largely supportive of patients' need to adjust SXB dosing to accommodate a change in routine and perceived the ability to adjust dosing as an important element of providing care. Further investigation is encouraged to understand SXB dosing guidance physicians provide to their patients. Support (If Any): Jazz Pharmaceuticals.